Equilibrium Studies on Some Binary Complexes of La(III), Ce(III), Pr(III) and Nd(III) with Ligands Containing N-N Donor Atoms - Pabreja, D.S.; A. Patel, Rashmikant; Sharma, Sangita; Vora, Jabli; Joshi, J.D. (Asian Journal of Chemistry, 2010)
The present paper describes a potentiometric study on formation constants of binary complexes of inner transition "4f' metal ions La(III), Ce(III), Pr(III) and Nd(III) with amines such as ethylenediamine, N-N-diroetbyl ethylenediamine, N-N-diethyl ethylenediamine, 1,2-diaminopropane and 1,3-diaminopropane carried out at constant temperature 30 ± 0.1 °C and ionic strength μ= 0.2 M dm-3 (NaCIO4). Various factors influencing the formation and stabilities of binary complexes have been discussed.